Risk Management of New Access Road Construction of Syamsuddin Noor Airport South Kalimantan Provincial Government (Case Study of East Access Development Plan) - Amin, Ahmad; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The risks involved in construction projects are numerous, but only a few risks need to be made a priority scale. Therefore, parties in the construction project need to give priority to important risks that will affect the profitability of the project. To find out the identification of the dominant risk in the project, it was carried out by distributing a questionnaire to 23 respondents consisting of 6 correspondents from the PUPR Office of South Kalimantan Province as the project owner, 12 respondents from service providers, and 5 respondents from supervisory consultants who were directly involved in the construction of the new access road project at Syamsudin Noor Airport. Based on the results of data analysis and validation involving experienced parties and directly involved in the construction of a new road west access to Syamsudin Noor Airport, 39 security risks were identified from 9 sources of risk, namely elements of Politics, Economic, Environment, Finance, Natural, project, Technical, Human and Safety . Judging from the analysis of the level of risk acceptance, the dominant risks in this study are unacceptable and undesirable. In terms of the impact of risk on project delays there are 4 risks (10%) unacceptable and 10 risks (26%) undesirable. In terms of the impact of risk on finances, there is 1 risk (3%) and 5 risks (13%) undesirable.